Dynamic analysis and experimental verification of the carbon–carbon composite finger seal under complex working states. (June 2019) - Wang, Li-Na; Wang, Yong; Sun, Heng-Chao; Ren, Guo-Hua; Sun, Li-Chen; Meng, Dong-Hui
The finger seal has an important influence on the performance of the aero-engine, and the effect of complex working states on the performance of the finger seal, which is located in the aero-engine, is also prominent. But so far, the finger seal performance under complex working states, which include the incline of the rotor, assembly condition, temperature effect, and impact effect, has not been investigated yet. Based on this, an equivalent dynamic model of finger seal is presented under complex working states, and the dynamic performance analysis of the finger seal is carried out by the model. The results show that the complex working states have larger influence on the finger seal performance. Meanwhile, an experimental research is carried out and the results are compared with the theoretical results. And then the validity of the equivalent dynamic model of the finger seal under complex working states is proved. The present work is conducive to improve the theoretical research system of finger seal, and promote the dynamic analysis technology to engineering application as well.